SEEKING AN ESCHATO-RELATIONAL FUTURE: - C.J. Kaunda (Acta Theologica)
In the context of relational spirituality, the article explores the possibility of decolonising Christian eschatology from the perspective of Zambian Bemba future imaginaries. It argues that, in order to reorder the social relations of any former colonised groups, it is imperative to decolonise their epistemic vision of the future and align it with the Missio Christis that encapsulates the eschato-relational vision. An eschato-relational future is proposed as one way of articulating the vision of the future informed by Bemba imaginaries.